Sending corporate social responsibility signals: What organizational characteristics must be met? - Ortega Carrasco, Pablo; Ferrón Vílchez, Vera (Review of Business Management, 2022)
Purpose – This work examines some of the organizational characteristics of companies that send CSR signals. It evaluates five determinants: operating in a highly polluting sector, concentration of ownership structure, corporate reputation, profitability, and size. Theoretical framework – This empirical research draws upon Signaling Theory and Neo-Institutional Theory. Design/methodology/approach – By using a combined methodology that analyzes the results of a qualitative comparative analysis and the results of a binary logistic regression model, covering a sample of 95 companies, this study reveals some important aspects of the profile of companies that send CSR signals to society. Findings – Larger or more profitable companies that operate in a highly polluting sector, have a non-concentrated ownership structure, and have a positive corporate reputation, tend to be more willing to send CSR signals. Furthermore, a positive corporate reputation is a key organizational characteristic for sending CSR signals. Practical & social implications of the research – Since sending CSR signals is a powerful tool for legitimizing a company’s CSR actions, a better understanding about this helps managers and regulators to know the organizational characteristics of companies interested in signaling. Originality/value – This study’s main contribution is to advance the knowledge on the profile of companies that decide to send CSR signals to society. The findings are especially valuable because it is argued that there are specific complementary organizational characteristics when the company decides to send CSR signals. Keywords – CSR signals, QCA, Signaling Theory, Neo-Institutional Theory, Global Reporting Initiative (GRI).